Chemical Changeability of Essential Oils in Chenpi and Qingpi from the Same Origin by Gas Chromatography-Mass Spectrometry Compiled with Automated Mass Spectral Deconvolution and Identification System - Wang, Jian; Liu, Youping; Chen, Hongping; Chen, Lin; Wei, Zheng; Liu, Rong; Long, Fei; Wan, Deguang (Asian Journal of Chemistry, 2013)
Chemical variability of essential oils in Chenpi or called pericarpium citri reticulatae and Qingpi or called pericarpium citri reticulatae viride from the same source was investigated by gas chromatography-mass spectrometry (GC-MS) compiled with automated mass spectral deconvolution and identification system. Pericarpium citri reticulatae viride and Pericarpium citri reticulatae were collected once a month during July-December in 2011 from the identical area and the cultivar as Citrus reticulata Dahongpao of C. reticulata blanco. The oil components were identified by their purified mass spectra and Kováts retention indices (RIs). A total of 67, 77, 66, 51, 46 and 59 compounds representing 89.856, 92.151, 97.881, 97.738, 97.229 and 97.897 % of their total relative contents, respectively in the oils of Pericarpium citri reticulatae viride and Pericarpium citri reticulatae were discerned. The oils from Pericarpium citri reticulatae viride and Pericarpium citri reticulatae varied considerably both qualitatively and quantitatively. Chemical changeability of six samples differed with each other, to a degree. The chemotype as D-limonene/g-terpinene/linalool (55.111-77.659 %/6.579-7.841 %/1.197-7.773 %) was differentiated for essential oils of Pericarpium citri reticulatae viride and Pericarpium citri reticulatae from C. reticulata Dahongpao. The study manifests automated mass spectral deconvolution and identification system can efficiently enhance the accuracy of quantitative and qualitative analyses by extracting information from chromatograms and mass spectra. The results have some meanings to clarify the similarities and differences in bioactive compounds as volatile oils of Pericarpium citri reticulatae viride and Pericarpium citri reticulatae and to expound the scientific essence of one material used as two kinds of Chinese materia medica such as Pericarpium citri reticulatae viride and Pericarpium citri reticulatae in the end.